Tanggung Jawab Perusahaan Pelayanan Pengiriman Barang terhadap Kerugian Atas Manipulasi Tarif Pengiriman Barang yang Merugikan Konsumen (Studi Kasus Putusan Mahkamah Agung Nomor 175 K/ Pdt.Sus-BPSK/2021) - Elysia Wilhelmina Rengkung; Ariawan Gunadi (Jurnal Hukum Lex Generalis, 2024)
This journal examines the responsibility of courier service companies for damages resulting from the manipulation of shipping rates that harm consumers, focusing on the case study of the Supreme Court Decision No. 175 K/Pdt.Sus-BPSK/2021. The research aims to identify and analyze the legal mechanisms for holding companies accountable in cases of rate manipulation and to understand the implications of the Supreme Court’s decision on business practices in the courier sector. The research employs a case study method with a qualitative approach, analyzing court documents and related data from the case discussed in the ruling. The findings indicate that courier companies have a legal obligation for rate transparency and accountability in pricing practices. Rate manipulation detrimental to consumers is deemed a violation of fairness and consumer protection principles. The Supreme Court’s decision reinforces the legal responsibility of companies and establishes an important precedent for handling similar disputes in the future. The conclusion emphasizes the need for stricter oversight of courier service companies and clearer regulations regarding rate transparency to protect consumer rights. This research aims to contribute to the development of consumer protection law and fairer business practices in Indonesia.